CIVIC V. NATIONAL STATE: A FALSE DILEMMA - Antic, Petar; Bašić, Goran (Pravni zapisi, 2026)
This paper critically reexamines the dichotomy between the civic state and the national state, arguing that it is both empirically inadequate and normatively misleading. It conceptualizes these approaches as normative models and highlights their internal limitations: the civic model may conceal cultural dominance, while the national model risks hierarchical inclusion. Through a comparative analysis of France, Serbia and Hungary, the paper examines their effects on social cohesion, ethnic distance and perceptions of discrimination. The findings show that neither model, when applied in isolation, ensures inclusive political belonging. The paper concludes that this dichotomy should be reconsidered in favor of a more nuanced approach combining universal rights and recognition of collective identities.
Keywords: civic state; national state; constitutional identity; minority rights; social cohesion; ethnic distance; discrimination; universalism; collective identity; comparative constitutional analysis